ANALYSIS OF THE INFLUENCE OF EXCHANGE RATE, INTEREST RATE, INFLATION AND MONEY SUPPLY (M2) ON INDONESIAN SYARIAH STOCK INDEX (ISSI) (EMPIRICAL STUDY 2006 - 2019) - Y, R. Roosaleh Laksono T.; Sonia, Nita; Triani, Dian; Adani, Syarafina; Nurahma, Putri; Yusuf, Sheptian (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to determine and analyze the influence of external factors in this case macroeconomic factors (exchange rate, interest rate, inflation, and money supply) on the Islamic stock price index on the Indonesia Stock Exchange from 2006 to 2019 during 15 years, both short-term equilibrium relationship and long-term equilibrium relationship. The results of research that have been carried out with several stages of statistical testing conclude that there has been a long-term equilibrium relationship where the partial relationship between the exchange rate, interest rate, money supply, and inflation in the long term affects the stock exchange, but the interest rate shows an unrelated relationship. significant and does not affect the stock exchange. Meanwhile, the short-term equilibrium relationship results from the cointegration test and error correction model test can be concluded that there is no short-term equilibrium relationship exchange rate, money supply, interest rate, and inflation on the stock exchange, meaning that the exchange rate, interest rate, money supply, and inflation in the short term does not affect the stock exchange.